Transmitted HIV-1 resistance in never exposed to antiretroviral therapy patients, Cali-Colombia 2008-2015 - María Victoria Coral-Orbes (Asociación Colombiana de Infectología, 2018)
Introduction: This study determined the frequency of transmitted drug resistance in patients not exposed to ART, attended in Cali-Colombia. Methodology: A cross-sectional study between 2008 and 2015 involved 342 patients older than 18 years, with confirmed HIV infection, without exposure to antiretrovirals, with resistance genotype prior to initiation of antiretroviral and informed consent. Resistance mutations defined by WHO-2009 and international AIDS Society-USA 2015 were included. Sociodemographic and clinical characteristics related to HIV were also collected. Results: The mean age was 32 ± 10.5 years; 74% were men. At the time of genotype, median viral load was 26,802 copies / mL, and 343 T-CD4 / mm3 cells. According to the WHO-2009 list, the frequency of mutations was 3.2% and considering the AIDS Society-USA list and the Stanford HIV database mutations, this reached 7.9%. The most common mutations were K103N/S (2.1%), Q58E (2%), V108I and E138A (1.2%). Reverse transcriptase mutations were found in 4.4% for non-nucleoside inhibitors and 1.2% for nucleoside; for protease inhibitors were 2.3%. In patients with retroviral infection <1 year, the transmitted resistances prevalence, using only the WHO-2009 list, reach 7.3%, while in those with ≥1 year only was 1.6% (p=0.008). Conclusions: The frequency of transmitted mutations in naïve patients with retroviral infection <1 year exceeded the prevalence threshold recommended by the WHO to implement the resistance genotype.